Prion protein facilitates synaptic vesicle release by enhancing release probability - Robinson, Susan W. (Oxford University Press, 2014)
The cellular prion protein (PrP(C)) has been implicated in several neurodegenerative diseases as a result of protein misfolding. In humans, prion disease occurs typically with a sporadic origin where uncharacterized mechanisms induce spontaneous PrP(C) misfolding leading to neurotoxic PrP-scrapie formation (PrP(SC)). The consequences of misfolded PrP(C) signalling are well characterized but little is known about the physiological roles of PrP(C) and its involvement in disease. Here we investigated wild-type PrP(C) signalling in synaptic function as well as the effects of a disease-relevant mutation within PrP(C) (proline-to-leucine mutation at codon 101). Expression of wild-type PrP(C) at the Drosophila neuromuscular junction leads to enhanced synaptic responses as detected in larger miniature synaptic currents which are caused by enlarged presynaptic vesicles. The expression of the mutated PrP(C) leads to reduction of both parameters compared with wild-type PrP(C). Wild-type PrP(C) enhances synaptic release probability and quantal content but reduces the size of the ready-releasable vesicle pool. Partially, these changes are not detectable following expression of the mutant PrP(C). A behavioural test revealed that expression of either protein caused an increase in locomotor activities consistent with enhanced synaptic release and stronger muscle contractions. Both proteins were sensitive to proteinase digestion. These data uncover new functions of wild-type PrP(C) at the synapse with a disease-relevant mutation in PrP(C) leading to diminished functional phenotypes. Thus, our data present essential new information possibly related to prion pathogenesis in which a functional synaptic role of PrP(C) is compromised due to its advanced conversion into PrP(SC) thereby creating a lack-of-function scenario.